2XXX Aluminum Lithium Alloy
The 2xxx aluminum lithium alloy composition addresses the challenge of enhancing strength and toughness in thick wrought products by optimizing copper, lithium, zinc, and manganese content, resulting in superior mechanical properties and corrosion resistance.
Patent Information
- Application Number
- JP2021523951
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-11-07
- Filing Date
- 2019-11-06
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2039-11-06
AI Technical Summary
Existing aluminum alloys face challenges in improving strength without compromising toughness and stress corrosion cracking resistance, particularly in thick wrought products.
A 2xxx aluminum lithium alloy composition with specific ranges of copper, lithium, zinc, manganese, magnesium, and crystal grain control elements, optimized for achieving improved strength, toughness, and stress corrosion resistance through controlled crystal grain structure.
The alloy achieves enhanced tensile yield strength, fracture toughness, and stress corrosion cracking resistance, outperforming conventional alloys like 2070, with improved properties in thick wrought products.
Smart Images

Figure 0007621248000012 
Figure 0007621248000013 
Figure 0007621248000014
Abstract
Description
[Technical Field]
[0001] The present disclosure relates to 2xxx aluminum-lithium alloys and products made therefrom. [Background technology]
[0002] Aluminum alloys are useful in a variety of applications. However, it is often difficult to improve one property of an aluminum alloy without degrading another property. For example, it is difficult to increase the strength of an alloy without decreasing its toughness. Other properties of interest for aluminum alloys include corrosion resistance and fatigue crack growth rate resistance, to name two. Summary of the Invention
[0003] Broadly, this patent application relates to new 2xxx aluminum-lithium alloys comprising (and in some cases consisting essentially of, or consisting of) 2.5-3.9 wt.% Cu, 0.82-1.20 wt.% Li, 0.5-2.0 wt.% Zn, 0.10-0.60 wt.% Mn, 0.05-0.35 wt.% Mg, 0.05-0.50 wt.% at least one grain structure control element, where the at least one grain structure control element is selected from the group consisting of Zr, Sc, Cr, V, Hf, other rare earth elements, and combinations thereof, up to 0.22 wt.% Ag, up to 0.15 wt.% Fe, up to 0.12 wt.% Si, and up to 0.15 wt.% Ti, with the balance being aluminum, incidental elements, and impurities. Products incorporating such alloy compositions may achieve, for example, improved combinations of two or more of strength, elongation, fracture toughness, and stress corrosion cracking resistance.
[0004] i.Composition As noted above, copper (Cu) is included in the alloy, generally in the range of 2.5 wt.% to 3.9 wt.% Cu. More specific embodiments regarding copper are provided near the end of this section.
[0005] As noted above, lithium (Li) is included in the alloy, generally in the range of 0.82% to 1.20% by weight. In one embodiment, the new alloy includes at least 0.85% Li by weight. In another embodiment, the new alloy includes at least 0.875% Li by weight. In yet another embodiment, the new alloy includes at least 0.90% Li by weight. In another embodiment, the new alloy includes at least 0.925% Li by weight. In another embodiment, the new alloy includes at least 0.95% Li by weight. In one embodiment, the new alloy includes no more than 1.15% Li by weight. In another embodiment, the new alloy includes no more than 1.10% Li by weight. In yet another embodiment, the new alloy includes no more than 1.075% Li by weight. In another embodiment, the new alloy includes no more than 1.050% Li by weight. In yet another embodiment, the new alloy includes no more than 1.025% Li by weight. In another embodiment, the new alloy includes no more than 1.000% Li by weight. In yet another embodiment, the new alloy includes up to 0.980 wt.% Li.
[0006] Zinc (Zn) is generally included in the new alloys, generally ranging from 0.50 wt. % Zn to 2.0 wt. % Zn. More specific embodiments regarding zinc are provided near the end of this section.
[0007] The weight ratio of copper to zinc in an alloy may be related to its improved properties (e.g., its quench sensitivity). In one embodiment, the new 2xxx aluminum alloys achieve a copper to zinc weight ratio of 4.25:1 (Cu:Zn) or less.
[0008] Manganese (Mn) is generally included in the new alloy, generally ranging from 0.10 wt. % to 0.60 wt. % Mn. In one embodiment, the new alloy includes at least 0.125 wt. % Mn. In another embodiment, the new alloy includes at least 0.15 wt. % Mn. In yet another embodiment, the new alloy includes at least 0.175 wt. % Mn. In another embodiment, the new alloy includes at least 0.20 wt. % Mn. In another embodiment, the new alloy includes at least 0.225 wt. % Mn. In yet another embodiment, the new alloy includes at least 0.25 wt. % Mn. In another embodiment, the new alloy includes at least 0.27 wt. % Mn. In one embodiment, the new alloy includes no more than 0.55 wt. % Mn. In another embodiment, the new alloy includes no more than 0.50 wt. % Mn. In yet another embodiment, the new alloy includes no more than 0.45 wt. % Mn. In another embodiment, the new alloy contains not more than 0.425 wt.% Mn. In yet another embodiment, the new alloy contains not more than 0.40 wt.% Mn. In another embodiment, the new alloy contains not more than 0.375 wt.% Mn. In yet another embodiment, the new alloy contains not more than 0.35 wt.% Mn. In another embodiment, the new alloy contains not more than 0.325 wt.% Mn. In another embodiment, the new alloy contains not more than 0.30 wt.% Mn. In the alloy industry, manganese is sometimes considered both an alloying element and a grain structure control element; manganese held in solid solution can enhance the mechanical properties (e.g., strength and / or toughness) of the alloy, while manganese in particulate form (e.g., Al6Mn, Al, which may also be referred to as dispersoids) can enhance the mechanical properties (e.g., strength and / or toughness) of the alloy. 12 Mn3Si2, Al 20 Cu2Mn3) may assist in grain structure control and may also improve grain damage tolerance, such as fracture toughness. However, in this patent application, Mn is defined separately with its own compositional limits and, therefore, is not within the definition of "grain structure control element" (described below) for purposes of this patent application.
[0009] Magnesium (Mg) is generally included in the new alloys, generally in the range of 0.05 wt.% to 0.35 wt.% Mg. More specific embodiments regarding magnesium are provided near the end of this section.
[0010] The alloy may include 0.05-0.50 wt. % of at least one grain structure control element selected from the group consisting of zirconium (Zr), scandium (Sc), chromium (Cr), vanadium (V), and / or hafnium (Hf), and / or other rare earth elements, whereby the utilized grain structure control element(s) are maintained below their maximum solubility. As used herein, "grain structure control element" means an element or compound that is an intentional alloy addition targeted at forming second-phase particles, usually in the solid state, to control changes in solid-state grain structure during thermal processes such as recovery and recrystallization. For purposes of this patent application, grain structure control elements include Zr, Sc, Cr, V, Hf, and other rare earth elements, to name a few, but exclude Mn.
[0011] The amount of grain structure control material utilized in the alloy generally depends on the type of material utilized in the grain structure control and / or alloy manufacturing process. In one approach, the grain structure control element is Zr, and the alloy includes 0.05% to 0.20% by weight of Zr. In one embodiment, the aluminum alloy includes at least 0.06% by weight of Zr. In another embodiment, the aluminum alloy includes at least 0.07% by weight of Zr. In yet another embodiment, the aluminum alloy includes at least 0.08% by weight of Zr. In one embodiment, the aluminum alloy includes not more than 0.18% by weight of Zr. In another embodiment, the aluminum alloy includes not more than 0.16% by weight of Zr. In another embodiment, the aluminum alloy includes not more than 0.15% by weight of Zr. In yet another embodiment, the aluminum alloy includes not more than 0.14% by weight of Zr. In another embodiment, the aluminum alloy includes not more than 0.13% by weight of Zr. In one embodiment, the alloy includes 0.05% to 0.15% by weight of Zr. In another embodiment, the alloy comprises between 0.07% and 0.14% by weight Zr, hi another embodiment, the alloy comprises between 0.08% and 0.13% by weight Zr.
[0012] The alloy may contain up to 0.15 wt.% Ti for grain refinement and / or other purposes. Grain refiners are inoculants or nuclei for seeding new grains during solidification of the alloy. One example of a grain refiner is a 9.525 mm rod containing 96% aluminum, 3% titanium (Ti), and 1% boron (B) (all weight percent), with virtually all of the boron present as finely dispersed TiB2 particles. During casting, the grain refiner rod may be fed in-line into the molten alloy flowing into the casting pit at a controlled rate. The amount of grain refiner included in the alloy generally depends on the type of material utilized in the grain refinement and alloy manufacturing process. Examples of grain refiners include Ti combined with B (e.g., TiB2) or carbon (TiC), although other grain refiners, such as Al-Ti master alloys, may be utilized. Generally, grain refiners are added to the alloy in amounts ranging from 0.0003 wt.% to 0.005 wt.%, depending on the desired as-cast grain size. Additionally, Ti can be added separately to the alloy in amounts up to 0.15 wt.%, depending on the product form, to increase the effectiveness of the grain refiner, typically ranging from 0.005 to 0.15 wt.% Ti. When Ti is included in the alloy, it is generally present in an amount of 0.01 to 0.10 wt.%. In one embodiment, the new alloy includes at least 0.005 wt.% Ti. In another embodiment, the new alloy includes at least 0.01 wt.% Ti. In yet another embodiment, the new alloy includes at least 0.015 wt.% Ti. In another embodiment, the new alloy includes at least 0.020 wt.% Ti. In one embodiment, the new alloy includes no more than 0.10 wt.% Ti. In another embodiment, the new alloy includes no more than 0.08 wt.% Ti. In yet another embodiment, the new alloy includes up to 0.07 wt.% Ti. In another embodiment, the new alloy includes up to 0.06 wt.% Ti. In yet another embodiment, the new alloy includes up to 0.05 wt.% Ti.In one embodiment, the aluminum alloy includes a grain refiner, wherein the grain refiner is at least one of TiB2 and TiC, and the wt% of Ti in the alloy is 0.01-0.06 wt%, or 0.01-0.03 wt%.
[0013] The new aluminum alloy may include iron (Fe). The iron content of the new alloy generally should not exceed 0.15 wt.%. In one embodiment, the new alloy may include at least 0.01 wt.% Fe. In one embodiment, the new alloy includes no more than 0.12 wt.% Fe. In another embodiment, the new alloy includes no more than 0.10 wt.% Fe. In yet another embodiment, the new alloy includes no more than 0.08 wt.% Fe. In another embodiment, the new alloy includes no more than 0.06 wt.% Fe. In yet another embodiment, the new alloy includes no more than 0.04 wt.% Fe.
[0014] The new aluminum alloy may include silicon (Si). The silicon content of the new alloy generally should not exceed 0.12 wt%. In one embodiment, the new alloy may include at least 0.01 wt% Si. In one embodiment, the new alloy includes no more than 0.10 wt% Si. In another embodiment, the new alloy includes no more than 0.08 wt% Si. In yet another embodiment, the new alloy includes no more than 0.06 wt% Si. In another embodiment, the new alloy includes no more than 0.04 wt% Si.
[0015] As noted above, the new aluminum alloy may optionally contain silver, and may contain silver in an amount of up to 0.22 wt.%. In one embodiment, the new alloy contains 0.20 wt.% or less of Ag. In another embodiment, the new alloy contains 0.15 wt.% or less of Ag. In yet another embodiment, the new alloy contains 0.10 wt.% or less of Ag. In another embodiment, the new alloy contains 0.05 wt.% or less of Ag. In yet another embodiment, the new alloy contains 0.01 wt.% or less of Ag. In another embodiment, the new alloy contains 0.005 wt.% or less of Ag and / or Ag is not detectable in the new alloy.
[0016] As noted above, the new alloy generally comprises the alloying components described, with the balance being aluminum, optional accessory elements, and impurities. As used herein, "accessory element" means an element or material, other than those listed above, that can be optionally added to an alloy to aid in the production of the alloy. Examples of accessory elements include casting aids such as grain refiners and deoxidizers. Optional accessory elements may be included in the alloy in a cumulative amount of up to 1.0 wt.%. As one non-limiting example, one or more accessory elements may be added to the alloy during casting to reduce or limit (and in some cases eliminate) cracking of the ingot due to, for example, oxide folds, pits, and oxide patches. These types of accessory elements are generally referred to herein as deoxidizers. Examples of some deoxidizers include Ca, Sr, and Be. When calcium (Ca) is included in the alloy, it is generally present in an amount of up to about 0.05 wt.%, or up to about 0.03 wt.%. In some embodiments, Ca is included in the alloy in an amount of about 0.001-0.03 wt. % or about 0.05 wt. %, such as 0.001-0.008 wt. % (or 10-80 ppm). Strontium (Sr) can be included in the alloy (in whole or in part) as a substitute for Ca, and thus can be included in the alloy in the same or similar amount as Ca. Traditionally, the addition of beryllium (Be) has helped reduce the tendency of ingots to crack, but for environmental, health, and safety reasons, some embodiments of the alloy are substantially Be-free. When Be is included in the alloy, it is generally present in an amount up to about 20 ppm. Accessory elements can be present in minor or significant amounts, and may themselves be desirable or add other characteristics without departing from the alloys described herein, so long as the alloy retains the desirable features described herein. However, it should be understood that the scope of the present disclosure should not / cannot be circumvented by the mere addition of a number of element(s) that may not otherwise affect the combination of properties desired and obtained herein.
[0017] The new 2xxx aluminum alloys generally contain small amounts of impurities. In one embodiment, the new 2xxx aluminum alloys contain no more than 0.15 wt.% total impurities, and the 2xxx aluminum alloys contain no more than 0.05 wt.% each of the impurities. In another embodiment, the new 2xxx aluminum alloys contain no more than 0.10 wt.% total impurities, and the 2xxx aluminum alloys contain no more than 0.03 wt.% each of the impurities.
[0018] a. First version of the new 2xxx aluminum alloy In one embodiment, a first version of the new 2xxx aluminum alloy includes a first tailored amount of copper, magnesium, and zinc. In one approach, the first version includes 3.1-3.8 wt.% copper, 0.5-2.0 wt.% Zn, and 0.05-0.35 wt.% Mg.
[0019] In one embodiment, the first version contains at least 3.2 wt.% Cu. In another embodiment, the first version contains at least 3.3 wt.% Cu. In one embodiment, the first version contains no more than 3.75 wt.% Cu. In another embodiment, the first version contains no more than 3.7 wt.% Cu. In one embodiment, the first version contains no more than 3.65 wt.% Cu. In another embodiment, the first version contains no more than 3.6 wt.% Cu.
[0020] In one embodiment, the first version contains at least 0.6% Zn by weight. In another embodiment, the first version contains at least 0.7% Zn by weight. In yet another embodiment, the first version contains at least 0.75% Zn by weight. In another embodiment, the first version contains at least 0.8% Zn by weight. In yet another embodiment, the first version contains at least 0.85% Zn by weight. In another embodiment, the first version contains at least 0.9% Zn by weight. In yet another embodiment, the first version contains at least 0.95% Zn by weight. In one embodiment, the first version contains no more than 1.8% Zn by weight. In another embodiment, the first version contains no more than 1.6% Zn by weight. In yet another embodiment, the first version contains no more than 1.4% Zn by weight. In another embodiment, the first version contains no more than 1.3% Zn by weight. In yet another embodiment, the first version contains no more than 1.2% Zn by weight. In another embodiment, the first version contains no more than 1.1% Zn by weight. In yet another embodiment, the first version contains no more than 1.05 wt. % Zn.
[0021] As discussed above, the copper to zinc weight ratio in the alloy can be related to its improved properties (e.g., its quench sensitivity). In one embodiment, the first version achieves a copper to zinc (weight) ratio of 4.25:1 (Cu:Zn) or less, i.e., the alloy's (wt. % Cu) / (wt. % Zn) is 4.25 or less. In another embodiment, the first version achieves a copper to zinc (weight) ratio of 4.10:1 or less. In yet another embodiment, the first version achieves a copper to zinc (weight) ratio of 4.00:1 or less. In another embodiment, the first version achieves a copper to zinc (weight) ratio of 3.90:1 or less. In yet another embodiment, the first version achieves a copper to zinc (weight) ratio of 3.80:1 or less. In another embodiment, the first version achieves a copper to zinc (weight) ratio of 3.78:1 or less.
[0022] In one embodiment, the first version contains at least 0.10 wt% Mg. In another embodiment, the first version contains at least 0.125 wt% Mg. In yet another embodiment, the first version contains at least 0.15 wt% Mg. In another embodiment, the first version contains at least 0.175 wt% Mg. In yet another embodiment, the first version contains at least 0.20 wt% Mg. In another embodiment, the first version contains at least 0.21 wt% Mg. In yet another embodiment, the first version contains at least 0.22 wt% Mg. In one embodiment, the first version contains no more than 0.325 wt% Mg. In another embodiment, the first version contains no more than 0.30 wt% Mg. In yet another embodiment, the first version contains no more than 0.29 wt% Mg. In another embodiment, the first version contains no more than 0.28 wt% Mg.
[0023] Various first version embodiments of the 2xxx alloys are provided below.
[0024] [Table 1]
[0025] [Table 2]
[0026] In one embodiment, the first version comprises 3.2-3.7 wt.% Cu, 0.85-1.15 wt.% Li, 0.75-1.25 wt.% Zn, with a Cu:Zn weight ratio of ≦4.25:1; 0.15-0.29 wt.% Mg, (X1, X2, X3, X4, or X5) wt.% Mn, ≦0.005 wt.% Ag, 0.05-0.15 wt.% Zr, and ≦0.10 wt.% Fe. ≦0.08 wt.% Si and 0.01-0.10 wt.% Ti, the balance being aluminum, optional incidental elements, and impurities; X1 is 0.15-0.40 (i.e., X1 wt.% Mn is 0.15-0.40 wt.% Mn); X2 is 0.15-0.30; X3 is 0.15-0.25; X4 is 0.20-0.40; and X5 is 0.25-0.35.
[0027] b. Second version of the new 2xxx aluminum alloy embodiment In one embodiment, the second version of the new 2xxx aluminum alloy includes second tailored amounts of copper, magnesium, and zinc. In one approach, the second version includes 2.5-3.4 wt.% copper, 0.5-2.0 wt.% Zn, and 0.05-0.35 wt.% Mg.
[0028] In one embodiment, the second version contains at least 2.6 wt% Cu. In another embodiment, the second version contains at least 2.7 wt% Cu. In yet another embodiment, the second version contains at least 2.8 wt% Cu. In another embodiment, the second version contains at least 2.85 wt% Cu. In one embodiment, the second version contains no more than 3.35 wt% Cu. In another embodiment, the second version contains no more than 3.3 wt% Cu. In one embodiment, the second version contains no more than 3.25 wt% Cu. In another embodiment, the second version contains no more than 3.2 wt% Cu. In another embodiment, the second version contains no more than 3.15 wt% Cu.
[0029] In one embodiment, the second version contains at least 0.6 wt% Zn. In another embodiment, the second version contains at least 0.8 wt% Zn. In yet another embodiment, the second version contains at least 1.0 wt% Zn. In another embodiment, the second version contains at least 1.1 wt% Zn. In yet another embodiment, the second version contains at least 1.2 wt% Zn. In another embodiment, the second version contains at least 1.3 wt% Zn. In one embodiment, the second version contains no more than 1.9 wt% Zn. In another embodiment, the second version contains no more than 1.8 wt% Zn. In yet another embodiment, the second version contains no more than 1.7 wt% Zn. In another embodiment, the second version contains no more than 1.6 wt% Zn. In yet another embodiment, the second version contains no more than 1.5 wt% Zn.
[0030] As noted above, the copper to zinc weight ratio in the alloy can be related to its improved properties (e.g., its quench sensitivity). In one embodiment, the second version achieves a copper to zinc (weight) ratio of 4.25:1 (Cu:Zn) or less, i.e., the alloy's (wt. % Cu) / (wt. % Zn) is 4.00:1 or less. In another embodiment, the second version achieves a copper to zinc (weight) ratio of 3.75:1 or less. In yet another embodiment, the second version achieves a copper to zinc (weight) ratio of 3.50:1 or less. In another embodiment, the second version achieves a copper to zinc (weight) ratio of 3.30:1 or less. In yet another embodiment, the second version achieves a copper to zinc (weight) ratio of 3.10:1 or less. In another embodiment, the second version achieves a copper to zinc (weight) ratio of 2.95:1 or less. In yet another embodiment, the second version achieves a copper to zinc (weight) ratio of 2.90:1 or less. In another embodiment, the second version achieves a copper to zinc ratio (by weight) of 2.75:1 or less. In another embodiment, the second version achieves a copper to zinc ratio (by weight) of 2.67:1 or less. In another embodiment, the second version achieves a copper to zinc ratio (by weight) of 2.50:1 or less. In another embodiment, the second version achieves a copper to zinc ratio (by weight) of 2.42:1 or less.
[0031] In one embodiment, the second version contains at least 0.10 wt% Mg. In another embodiment, the second version contains at least 0.12 wt% Mg. In yet another embodiment, the second version contains at least 0.13 wt% Mg. In another embodiment, the second version contains at least 0.14 wt% Mg. In yet another embodiment, the second version contains at least 0.15 wt% Mg. In another embodiment, the second version contains at least 0.16 wt% Mg. In yet another embodiment, the second version contains at least 0.17 wt% Mg. In one embodiment, the second version contains no more than 0.30 wt% Mg. In another embodiment, the second version contains no more than 0.275 wt% Mg. In yet another embodiment, the second version contains no more than 0.25 wt% Mg. In another embodiment, the second version contains no more than 0.24 wt% Mg. In yet another embodiment, the second version contains no more than 0.23 wt% Mg.
[0032] Various second version embodiments of the new 2xxx alloys are provided below.
[0033] [Table 3]
[0034] [Table 4]
[0035] In one embodiment, the second version comprises 2.7-3.3 wt% Cu, 0.85-1.15 wt% Li, 1.2-1.6 wt% Zn, with a Cu:Zn weight ratio of ≦4.25:1, 0.15-0.30 wt% Mg, (Y1, Y2, Y3, Y4, or Y5) wt% Mn, ≦0.005 wt% Ag, 0.05-0.15 wt% Zr, ≦0.10 wt% Fe, and ≦ 0.08 wt% Si and 0.01-0.10 wt% Ti, the balance being aluminum, optional incidental elements, and impurities, Y1 is 0.15-0.40 (i.e., Y1 wt% Mn is 0.15-0.40 wt% Mn), Y2 is 0.15-0.30, Y3 is 0.15-0.25, Y4 is 0.20-0.40, and Y5 is 0.25-0.35.
[0036] ii. Product form The new alloys may be useful in a variety of product forms, including, for example, ingots or billets, wrought product forms (plate, forgings, and extrusions), molded castings, additively manufactured products, and powder metallurgy products.
[0037] In one embodiment, the new 2xxx aluminum alloy is in the form of a thick wrought product. The thick wrought aluminum alloy product is a wrought product having a cross-sectional thickness of at least 12.7 mm. The wrought product may be a rolled product, a forged product, or an extruded product. In one embodiment, the thick wrought aluminum alloy product has a thickness of at least 25.4 mm. In another embodiment, the thick wrought aluminum alloy product has a thickness of at least 50.8 mm. In yet another embodiment, the thick wrought aluminum alloy product has a thickness of at least 76.2 mm. In another embodiment, the thick wrought aluminum alloy product has a thickness of at least 101.6 mm. In yet another embodiment, the thick wrought aluminum alloy product has a thickness of at least 126.0 mm. In another embodiment, the thick wrought aluminum alloy product has a thickness of at least 152.4 mm. The improved properties described herein may be achieved in thick wrought aluminum alloy products having a thickness of up to 304.8 mm. In one embodiment, the thick wrought aluminum alloy product has a thickness of 254.0 mm or less. In another embodiment, the thick wrought aluminum alloy product has a thickness of 203.2 mm or less. In yet another embodiment, the thick wrought aluminum alloy product has a thickness of 177.8 mm or less. As used in this paragraph, thickness refers to the minimum thickness of the product, and it is understood that some portions of the product may achieve a thickness slightly greater than the stated minimum.
[0038] iii. Training process The new alloys can be prepared in the appropriate temper for the wrought form by more or less conventional methods, including direct chill (DC) casting of the aluminum alloy into ingot form. After conventional skinning, lathing, or peeling (if necessary), and homogenization, which can be completed before or after skinning, these ingots can be further processed by hot working the product. The product can then be optionally cold worked, optionally annealed, solution heat treated, quenched, and final cold worked (e.g., by 0.5% to 10% stretch or compression). After the final cold working step, the product can be artificially aged. Thus, in some embodiments, the product can be manufactured in a T3 or T8 temper. In other embodiments, other T tempers (e.g., any of the T1, T2, T4, T5, T6, T7, or T9 tempers) can be used. The T tempers are defined in ANSI H35.1 (2009).
[0039] iv.Characteristics The new 2xxx aluminum-lithium alloys generally provide improved combinations of at least two of strength, elongation, fracture toughness, and stress corrosion cracking resistance.
[0040] In one embodiment, the new 2xxx aluminum lithium alloy has a thickness of at least 80 mm and achieves a tensile yield strength (ST) of at least 440 MPa in the T8 temper. In another embodiment, the new 2xxx aluminum lithium alloy has a thickness of at least 80 mm and achieves a tensile yield strength (ST) of at least 450 MPa in the T8 temper. In yet another embodiment, the new 2xxx aluminum lithium alloy has a thickness of at least 80 mm and achieves a tensile yield strength (ST) of at least 460 MPa in the T8 temper. In another embodiment, the new 2xxx aluminum lithium alloy has a thickness of at least 80 mm and achieves a tensile yield strength (ST) of at least 470 MPa in the T8 temper. In yet another embodiment, the new 2xxx aluminum lithium alloy has a thickness of at least 80 mm and achieves a tensile yield strength (ST) of at least 480 MPa or greater in the T8 temper. The above strength properties may be achieved in products having a thickness of at least 100 mm, or at least 125 mm, or at least 150 mm or greater.
[0041] In one embodiment, the new 2xxx aluminum lithium alloy has a thickness of at least 80 mm and a plane strain (K) of at least 20 MPa-sqrt-m in the T8 temper. IC In another embodiment, the new 2xxx aluminum lithium alloys have a thickness of at least 80 mm and achieve a plane strain (K) of at least 21 MPa-sqrt-m in the T8 temper. IC In yet another embodiment, the new 2xxx aluminum lithium alloys have a thickness of at least 80 mm and achieve a plane strain (K) of at least 22 MPa-sqrt-m in the T8 temper. IC In another embodiment, the new 2xxx aluminum lithium alloys have a thickness of at least 80 mm and achieve a plane strain (K ) fracture toughness (SL) of at least 23 MPa-sqrt-m in the T8 temper. ICIn yet another embodiment, the new 2xxx aluminum lithium alloys have a thickness of at least 80 mm and achieve a plane strain (K) of at least 24 MPa-sqrt-m in the T8 temper. IC In another embodiment, the new 2xxx aluminum lithium alloys have a thickness of at least 80 mm and achieve a plane strain (K) of at least 25 MPa-sqrt-m in the T8 temper. IC In yet another embodiment, the new 2xxx aluminum lithium alloys have a thickness of at least 80 mm and a plane strain (K) fracture toughness (SL) of at least 26 MPa-sqrt-m or greater in the T8 temper. IC ) fracture toughness (SL). The above fracture toughness properties may be achieved in products having a thickness of at least 100 mm, or at least 125 mm, or at least 150 mm or more.
[0042] In one embodiment, the new 2xxx aluminum lithium alloy has a thickness of at least 80 mm and achieves an elongation (ST) of at least 1.5% in the T8 temper. In another embodiment, the new 2xxx aluminum lithium alloy has a thickness of at least 80 mm and achieves an elongation (ST) of at least 2.0% in the T8 temper. In yet another embodiment, the new 2xxx aluminum lithium alloy has a thickness of at least 80 mm and achieves an elongation (ST) of at least 2.5% in the T8 temper. In one embodiment, the new 2xxx aluminum lithium alloy has a thickness of at least 80 mm and achieves an elongation (ST) of at least 3.0% or greater in the T8 temper. The above elongation properties may be achieved in products having a thickness of at least 100 mm, or at least 125 mm, or at least 150 mm or greater.
[0043] In one embodiment, the new 2xxx aluminum-lithium alloy has a thickness of at least 80 mm, is T8 tempered, and is stress corrosion cracking resistant (as defined below). The above stress corrosion cracking resistance property may be achieved in products having thicknesses of at least 100 mm, or at least 125 mm, or at least 150 mm or more.
[0044] In one approach, the new 2xxx aluminum-lithium alloys have at least 3.0 MPa-sqrt-m (MPa√m) higher plane strain (K) compared to standard 2070 aluminum alloy products when both products are processed to the same product form, gauge, yield strength, and temper. IC For example, if both the new 2xxx aluminum-lithium alloys and the 2070 alloy are manufactured as 150 mm plates in the T8 temper (having the same amount of stretch or compression, e.g., within 0.5% of each other), and both alloys are artificially aged to approximately the same tensile yield strength (e.g., within 5 MPa of each other), this approach will achieve the K of the new 2xxx aluminum-lithium alloys. IC The fracture toughness will be at least 3 MPa-sqrt-m higher than that of 2070 alloy. In one embodiment, the new 2xxx aluminum-lithium alloys will have at least 4.0 MPa-sqrt-m higher plane strain (K) than standard 2070 aluminum alloy products when both products are processed to the same product form, gauge, yield strength, and temper. IC In another embodiment, the new 2xxx aluminum-lithium alloys achieve a plane strain (K ) fracture toughness that is at least 5.0 MPa-sqrt-m higher than that of a standard 2070 aluminum alloy product when both products are processed to the same product form, gauge, yield strength, and temper. IC) fracture toughness. Standard 2070 aluminum alloy products nominally contain (target) 3.5 wt.% Cu, 0.30 wt.% Mn, 0.22 wt.% Mg, 0.30 wt.% Zn, 1.15 wt.% Li, 0.30 wt.% Zn, 0.11 wt.% Zr, ≦0.04 wt.% Si, ≦0.06 wt.% Fe, ≦0.03 wt.% Ti, impurities totaling ≦0.10 wt.% and ≦0.03 wt.% each, the balance being aluminum.
[0045] While the above properties generally relate to thick plate products, similar properties can also be achieved in thick forged and thick extruded products. Furthermore, many of the above properties can be achieved in combination, as illustrated by the following examples.
[0046] v.Definition Unless otherwise indicated, the following definitions apply in this application.
[0047] "2xxx aluminum alloys" are aluminum alloy compositions having copper as the major alloying element, as defined by the Aluminum Association in "International Alloy Designations and Chemical Composition Limits for Wrought Aluminum and Wrought Aluminum Alloys," p. 28 (2015). For purposes of this patent application, 2xxx aluminum alloy compositions may be used for non-wrought products such as molded castings, ingots / billets, and additively manufactured products, among others.
[0048] "Wrought aluminum alloy product" means an aluminum alloy product that is hot worked after casting, and includes rolled products (sheet or plate), forged products, and extruded products.
[0049] "Wrought aluminum alloy product" means a wrought aluminum alloy product that is either die-forged or hand-forged.
[0050] "Solution heat treatment" means exposing an aluminum alloy to elevated temperatures for the purpose of putting the solute(s) into solid solution.
[0051] "Hot working" means working the aluminum alloy product at an elevated temperature, generally at least 250°F.
[0052] "Cold working" means working an aluminum alloy product at temperatures that are not considered hot working temperatures, generally below about 250°F (e.g., ambient temperature).
[0053] "Artificial aging" means exposing an aluminum alloy to elevated temperatures for the purpose of precipitating a solute or solutes. Artificial aging can be carried out in one or more steps, which may involve varying the temperature and / or exposure time.
[0054] Strength and elongation are measured according to ASTM E8 and B557.
[0055] Fracture toughness is measured according to ASTM E399.
[0056] "Stress corrosion cracking resistance" means that no specimen of the 2xxx aluminum alloy product fails after a 30-day alternating immersion test at a net stress of 379 MPa in accordance with ASTM G44 / G47, and the test requires at least five specimens. In one embodiment, no specimen of the 2xxx aluminum alloy product fails after a 60-day alternating immersion test at a net stress of 379 MPa in accordance with ASTM G44 / G47, and the test requires at least five specimens. In another embodiment, no specimen of the 2xxx aluminum alloy product fails after a 90-day alternating immersion test at a net stress of 379 MPa in accordance with ASTM G44 / G47, and the test requires at least five specimens. Specimens for SCC testing are extracted so that they are centered on the midplane and oriented in the ST direction relative to the original alloy product.
[0057] As used herein, "additive manufacturing" means "a process of joining materials, usually layer by layer, to create an object from 3D model data, as opposed to subtractive manufacturing methods," as defined in ASTM F2792-12a, entitled "Standard Terminology for Additive Manufacturing Technologies." Non-limiting examples of additive manufacturing processes useful for producing aluminum alloy products include, for example, DMLS (direct metal laser sintering), SLM (selective laser melting), SLS (selective laser sintering), and EBM (electron beam melting). Any suitable feedstock made from the new 2xxx aluminum alloys described above can be used, including one or more powders, one or more wires, one or more sheets, and combinations thereof. In some embodiments, the additive manufacturing feedstock consists of one or more powders comprising the new 2xxx aluminum alloys. Shavings are a type of particle. In some embodiments, the additive manufacturing feedstock consists of one or more wires comprising the new 2xxx aluminum alloys. Ribbons are a type of wire. In some embodiments, the additive manufacturing feedstock consists of one or more sheets comprising the new 2xxx aluminum alloys. Foil is a type of sheet.
[0058] These and other aspects, advantages, and novel features of this new technology are set forth in part in the description that follows, and will become apparent to those skilled in the art upon examination of the following description and drawings, or may be learned by practicing one or more embodiments of the technology provided by this disclosure.
[0059] The drawings constitute a part of this specification, include exemplary embodiments of the present disclosure, and illustrate various objects and their features. Additionally, any measurements, specifications, etc. shown in the drawings are intended to be illustrative and not limiting. Therefore, specific structural and functional details disclosed herein should not be construed as limiting, but merely as representative basis for teaching those skilled in the art to variously use the present invention.
[0060] Among the benefits and improvements disclosed, other objects and advantages of the present invention will become apparent from the following description taken in conjunction with the accompanying drawings. Detailed embodiments of the present invention are disclosed herein. However, it should be understood that the disclosed embodiments are merely exemplary of the invention, which may be embodied in various forms. Furthermore, the examples given in connection with the various embodiments of the present invention are intended to be illustrative and not limiting.
[0061] Throughout the specification and claims, the following terms take the meanings explicitly associated therewith unless the context clearly dictates otherwise. As used herein, the phrases "in one embodiment" and "in some embodiments" do not necessarily refer to the same embodiment, although they may. Additionally, as used herein, the phrases "in another embodiment" and "in some other embodiments" do not necessarily refer to different embodiments, although they may. Thus, various embodiments of the invention can be readily combined without departing from the scope or spirit of the invention.
[0062] Additionally, as used herein, the term "or" is an inclusive "or" operator and is equivalent to the term "and / or" unless the context clearly dictates otherwise (e.g., "X1, X2, X3, X4, or X5" does not mean "and / or" herein because all of X1 through X5 are unique and different from one another). The term "based on" is not exclusive and may be based on additional unstated factors unless the context clearly dictates otherwise. Additionally, throughout this specification, the meanings of "a," "an," and "the" include plural references unless the context clearly dictates otherwise. The meaning of "in" includes "in" and "on" unless the context clearly dictates otherwise.
[0063] While several embodiments of the present invention have been described, it should be understood that these embodiments are illustrative only, and not limiting, and that numerous modifications may be apparent to those skilled in the art. Moreover, unless the context clearly requires, the various steps may be performed in any desired order, and any applicable steps may be added and / or removed. [Brief explanation of the drawings]
[0064] [Figure 1] FIG. 1 is a graph showing the performance of various aluminum alloy products of Example 1. [Figure 2] FIG. 2 is a graph showing the performance of various aluminum alloy products of Example 1. [Figure 3] FIG. 3 is a graph showing the performance of various aluminum alloy products of Example 2. DETAILED DESCRIPTION OF THE INVENTION
[0065] Example 1 - Plate Test Various Al-Li alloys were cast as ingots and homogenized. The compositions of each ingot are shown in Table 3a below. Alloys A and B are invention alloys. Alloys C and 2070 alloy are non-invention alloys. Alloy 2070 is described, for example, in commonly owned U.S. Patent Application Publication No. 2012 / 0225271.
[0066] [Table 5]
[0067] The balance of each alloy was aluminum, incidental elements, and impurities, with no single impurity exceeding 0.05 wt.% and the total amount of impurities not exceeding 0.15 wt.%. After homogenization, the alloys were hot rolled to final gauge, solution heat treated, quenched, and stretched approximately 6%. The approximate final gauge is provided in Table 3b below.
[0068] [Table 6]
[0069] Various two-step artificial aging procedures were completed on the alloys, with the first step completed at 290°F (143.3°C) for various times as provided in Table 4 below, and the second step at 225°F (107.2°C) for 12 hours. Various mechanical properties of the aged aluminum alloy plates are measured according to ASTM E8 and B557. Fracture toughness properties of some samples were also measured and according to ASTM E399. As shown by the data below and the corresponding Figures 1 and 2, the alloys of the present invention achieved an improved combination of properties in the short transverse direction.
[0070] [Table 7]
[0071] At 100 mm, the new alloys generally achieve improved fracture toughness at comparable strengths. For example, inventive alloy A-1 achieves approximately 3 MPa-sqrt-m higher strength (after 30 hours of aging) than 2070 alloy at roughly comparable strengths. Inventive alloy A-2 also offers an improvement over 2070 alloy, and A-2 alloy is expected to achieve results similar to those of alloy A-1 if the silicon content of A-2 alloy is reduced to 0.02 wt.%. Inventive alloy B achieves significantly higher fracture toughness at reduced strength levels, but is expected to achieve results at least equivalent to A-1 when aged to comparable strengths. The improved properties are even more pronounced at 150 mm, where all of the inventive alloys achieve significantly better fracture toughness at comparable strengths. Notably, the inventive alloys contain less magnesium than non-inventive alloy C. The alloys of the present invention also have a Cu:Zn ratio (by weight) of 4.25:1 or less, while the non-invention alloys achieve higher Cu:Zn ratios. The alloys of the present invention also have more zinc than Alloy C and non-invention Alloy 2070.
[0072] The stress corrosion cracking (SCC) resistance properties of many alloys were tested in the ST orientation and according to ASTM G44 / G47. All of the alloys of the present invention achieved, or were expected to achieve, all aging conditions without any failures at net stresses of 310 MPa and 379 MPa over the 30-day test period (some alloys are still undergoing testing). Conversely, alloy C failed multiple times at net stresses of 310 MPa and 379 MPa within the 30-day period and under the same test conditions. This may be due to the fact that alloy C's high magnesium content may make it more susceptible to stress corrosion cracking. Alloy C could be further aged to improve corrosion resistance, but its already poor fracture toughness would be reduced. Conversely, alloys A and B of the present invention achieve a good combination of the four properties of strength, elongation, fracture toughness, and stress corrosion cracking resistance.
[0073] Example 2 - Additional Plate Testing Three additional Al-Li alloys (all invention alloys) were cast as ingots and homogenized, the compositions of which are shown in Table 5 below.
[0074] [Table 8]
[0075] The balance of each alloy was aluminum, incidental elements, and impurities, with no single impurity exceeding 0.05 wt.% and the total amount of impurities not exceeding 0.15 wt.%. After homogenization, the alloys were hot rolled to final gauge, solution heat treated, quenched, and then stretched approximately 6%. The alloys were then artificially aged at various times and temperatures. The aging conditions are shown in Table 6.
[0076] [Table 9]
[0077] The alloy was cooled to room temperature between the ageing steps.
[0078] The alloys were then tested for through-thickness mechanical properties, the results of which are shown in Table 7 below.
[0079] [Table 10]
[0080] As shown in Figure 3, Alloys 1 and 2 at thicknesses of approximately 60 mm achieve an excellent combination of strength and fracture toughness. Alloy 3 achieves a similar strength-toughness trend as the 100 mm alloy of Example 1.
[0081] The stress corrosion cracking (SCC) resistance properties of many of the alloys were also tested at a net stress of 310 MPa in the ST orientation as in Example 1. The results are provided in Table 8 below.
[0082] [Table 11]
[0083] While various embodiments of the present disclosure have been described in detail, it is apparent that variations and modifications of these embodiments will occur to those skilled in the art, but it should be expressly understood that such variations and modifications are within the spirit and scope of the present disclosure.
Claims
1. 2xxx aluminum alloys, 2.5 to 3.9 wt.% Cu; 0.82 to 1.20 wt.% Li; 0.75 to 2.0 wt. % Zn; 0.10 to 0.60 wt. % Mn; 0.05 to 0.35 wt. % Mg; 0.05-0.50 wt. % of at least one grain structure control element, said at least one grain structure control element being selected from the group consisting of Zr, Sc, Cr, V, Hf, other rare earth elements, and combinations thereof; Maximum 0.22 wt.% Ag; Maximum 0.15 wt.% Fe; Maximum 0.12 wt.% Si; and max 0.15 wt.% Ti, 2xxx aluminum alloys, the balance being aluminum, incidental elements, and impurities in a total amount of up to 0.15 wt.%, each of the impurities being not more than 0.05 wt.%, the incidental elements being up to 0.05 wt.% Ca, up to 0.05 wt.% Sr, and up to 20 ppm Be.
2. 2. The 2xxx aluminum alloy of claim 1, wherein the 2xxx aluminum alloy contains less than or equal to 0.20 wt.% Ag, or less than or equal to 0.15 wt.% Ag, or less than or equal to 0.10 wt.% Ag, or less than or equal to 0.05 wt.% Ag, or less than or equal to 0.01 wt.% Ag, or less than or equal to 0.005 wt.% Ag.
3. 2. The 2xxx aluminum alloy of claim 1, wherein the 2xxx aluminum alloy contains at least 0.85 wt.% Li, or at least 0.875 wt.% Li, or at least 0.900 wt.% Li, or at least 0.925 wt.% Li, or at least 0.950 wt.% Li.
4. 4. The 2xxx aluminum alloy of claim 3, wherein the 2xxx aluminum alloy contains less than or equal to 1.15 wt.% Li, or less than or equal to 1.10 wt.% Li, or less than or equal to 1.075 wt.% Li, or less than or equal to 1.050 wt.% Li, or less than or equal to 1.025 wt.% Li, or less than or equal to 1.000 wt.% Li, or less than or equal to 0.980 wt.% Li.
5. 2. The 2xxx aluminum alloy of claim 1, wherein (wt.% Cu) / (wt.% Zn) is less than or equal to 4.
25.
6. 2. The 2xxx aluminum alloy of claim 1, wherein the 2xxx aluminum alloy contains 3.1-3.8 wt.% Cu.
7. 7. The 2xxx aluminum alloy of claim 6, wherein the 2xxx aluminum alloy contains at least 0.80 wt.% Zn, or at least 0.85 wt.% Zn, or at least 0.9 wt.% Zn, or at least 0.95 wt.% Zn.
8. 8. The 2xxx aluminum alloy of claim 7, wherein the 2xxx aluminum alloy contains up to 1.8 wt.% Zn, or up to 1.6 wt.% Zn, or up to 1.4 wt.% Zn, or up to 1.3 wt.% Zn, or up to 1.2 wt.% Zn, or up to 1.1 wt.% Zn, or up to 1.05 wt.% Zn.
9. 7. The 2xxx aluminum alloy of claim 6, wherein the 2xxx aluminum alloy contains at least 0.10 wt.% Mg, or at least 0.125 wt.% Mg, or at least 0.15 wt.% Mg, or at least 0.175 wt.% Mg, or at least 0.20 wt.% Mg, or at least 0.21 wt.% Mg, or at least 0.22 wt.% Mg.
10. 10. The 2xxx aluminum alloy of claim 9, wherein the 2xxx aluminum alloy contains up to 0.325 wt.% Mg, or up to 0.30 wt.% Mg, or up to 0.29 wt.% Mg, or up to 0.28 wt.% Mg.
11. 7. The 2xxx aluminum alloy of claim 6, wherein (wt.% Cu) / (wt.% Zn) is equal to or less than 4.10, or equal to or less than 4.00, or equal to or less than 3.90, or equal to or less than 3.80, or equal to or less than 3.
78.
12. 2. The 2xxx aluminum alloy of claim 1, wherein the 2xxx aluminum alloy contains 2.5-3.4 wt. % Cu.
13. 13. The 2xxx aluminum alloy of claim 12, wherein the 2xxx aluminum alloy contains at least 0.8 wt.% Zn, or at least 1.0 wt.% Zn, or at least 1.1 wt.% Zn, or at least 1.2 wt.% Zn, or at least 1.3 wt.% Zn.
14. 14. The 2xxx aluminum alloy of claim 13, wherein the 2xxx aluminum alloy contains up to 1.9 wt.% Zn, or up to 1.8 wt.% Zn, or up to 1.7 wt.% Zn, or up to 1.6 wt.% Zn, or up to 1.5 wt.% Zn.
15. 13. The 2xxx aluminum alloy of claim 12, wherein the 2xxx aluminum alloy contains at least 0.10 wt.% Mg, or at least 0.12 wt.% Mg, or at least 0.13 wt.% Mg, or at least 0.14 wt.% Mg, or at least 0.15 wt.% Mg, or at least 0.16 wt.% Mg, or at least 0.17 wt.% Mg.
Citation Information
Patent Citations
Al-Cu-Li alloy product suitable for aerospace application
CN101855376A
Aluminum alloy for load cell
JP1991107440A
High strength al-li alloy excellent in SCC resistance
JP1992337044A
Ultra-high-strength aluminum alloy
JP1993503737A
Al-cu-li alloy with improved cryogenic fracture toughness
JP1997501203A